رؤيةُ العالَمِ بوصفها أداةً إجرائية لمقاربة الحداثة - نصر الدين بن سراي (International Institute of Islamic Thought, 2018)
يعرض البحث لمسألة الحداثة التي تعني جملة من التصوُّرات الفكرية التي نشأت في الغرب خلال حقبة لا تقل عن قرنين من الزمان، مُبيِّناً أن سبر أفكار الحداثة التي ما تزال تُسهِم في تشكيل الحضارة الغربية يتطلَّب عُدَّة منهجية، في عصرٍ تتعدد فيه المناهج وتتنوع بحسب التخصصات. ومن بين المناهج الجديدة التي نحاول استخدامها في دراسة الفكر الفلسفي الحداثي ما نُسمِّيه "رؤية العالَم" بوصفها أداةً إجرائيةً تُسهِّل علينا عملية المساءلة، وممارسة النقد، وتوجيه حزمة من الأسئلة تختصّ بالمشروع الحداثي وتصوُّراته عن العالَم. ويهدف البحث إلى إثبات أن الحداثة هي رؤية تضم في مكنونها بنى فكرية نسعى إلى اكتشافها من أجل النقد، وأنها تدّعي الكونية وأنها تحمل الخلاص.   Worldview as a Procedural Instrument to Approach Modernity Nasruddin Ben Serai Abstract The paper deals with the issue of modernity which is known to have certain intellectual perceptions that has developed in the West during two centuries or more. Modernity continues to shape Western civilization; the exploration of its ideas requires certain methodological equipment, especially in this age of multiple approaches and specialties. Worldview is one of the new approaches that is being used in the study of modern philosophical thought. Worldview is considered as a procedural instrument that facilitates raising questions and practicing criticism of modernity project and its perception of the world. The purpose of the study is to prove that modernity is a worldview that includes certain intellectual structures to be discovered and criticized, in order to deal with modernity's claims of universality and its possibility of providing salvation.